(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
The history of biosystematics research and its impacts on climate goes before political ramifications. Climate change is altering the environments and likely to result in changes in the distribution of species, flowering times; migrate and adapt to the new environmental conditions; or extinction. Adaptive capacity is the ability of the plants to adapt to the impacts of climate change. Adaptation process is going in nature through phenotypic plasticity, natural selection or migration or polyploidization. The options are not mutually exclusive. Phenotypic plasticity may be the most efficient way of adaptation to a new environment. Polyploidization may increase tolerance to diverse ecological conditions and the high incidence of polyploidy in plants indicates its adaptive significance. Population having polyploid pillar complex is a good backup support towards microevolution and speciation, a mode of adaptation. The paper discusses about these biosystematics approaches towards adaptation to new environmental conditions resulting from climate change. It also discusses about the role of taxonomists under the changed circumstances. It is evident from the review that a set of biosystematics data along with other ecological and conservation information needs to be included in Flora and Monographs. It reveals that it was as far as worked out at the Paris Botanical Congress 1954 and put up by Stebbins in a series of proposals, termed as “Stebbins’ Ten Points” that needs further enrichment. Bangladesh J. Plant Taxon. 28(1): 277-287, 2021 (June)